Contribution of Assurance and Responsiveness to Purchase Decisions: The Significance of Relationship Quality as an Intervening Variable - Riswandi, Nairufar Rahmatika; Firdaus, Firdaus; Nurhayati, Nurhayati; Syafaq, Shandya Aissy (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study examines the impact of assurance and responsiveness on the purchasing decisions of Tokopedia consumers in Semarang, with relationship quality as a mediating variable. In the context of increasingly fierce e-commerce competition, it is important to understand the factors that influence purchasing decisions in order to enhance the customer experience. This type of research is explanatory with a quantitative approach, involving 100 Tokopedia users as respondents. Data was collected through questionnaires and analyzed using SmartPLS 4. The findings show that assurance has a positive and significant impact on purchasing decisions, while responsiveness provides smaller benefits. The quality of relationships has proven to be a significant mediator, strengthening the influence of certainty and responsiveness in the decision-making process. The results of this study emphasize the importance of building trustful relationships with customers to improve service quality and reduce complaints on the Tokopedia platform, which can ultimately enhance customer loyalty. This research provides insights for e-commerce practitioners on strategies to enhance customer relationships through assurance and responsiveness.